MODELING AND ANALYSIS OF ELECTROMAGNETIC INTERFERENCE IN GROUNDING CIRCUITS OF CONTROL SYSTEMS (Лучшие интеллектуальные исследования, 2025)
Abstract:This paper analyzes the impact of electromagnetic interference caused by improperly designed grounding systems. A simplified model is proposed that includes receivers and equipment as sources of interference, allowing assessment of its effects on overall system performance. The presence of special circuit filters defines the boundary frequency bands for interference evaluation. It is shown that reducing the length of grounding conductors minimizes voltage drops caused by inductive reactance. In high-inductance conductors, interference increases proportionally with frequency and conductor length. The study also explores the effects of mutual electromagnetic induction between closely spaced conductors and quantifies the induced EMF.